TEACHER’S TALK ROLE IN TEACHING SPEAKING - Bayu Hendro Wicaksono (Proceedings of ISELT FBS Universitas Negeri Padang, 2016)
In the teaching learning process, scholars need to consider so many things. The two biggest things are students and teachers. Teachers as the focus of the present study are required to have many strategies in teaching. Consequently, speaking subject teachers need to speak actively in teaching and learning process and may use teacher’s talk to encourage the students to speak and respond the instructions in the speaking class actively. The objective of this present study was to investigate whether teacher’s talk exist in speaking class and to analyze the most dominant teacher’s talk element used by the teacher and the teacher’s reason to use it. Xiao-yan (2006) defines teacher talk (TT) as the kind of language used by the teacher for instruction in the classroom. In English teaching and learning, when a teacher just talks to their students and if their students understand, they are not only giving the lesson about the subject, but also may be giving the best language lesson (Hariyanti, 2005). Located at University of Muhammadiyah Malang, this present study used qualitative narrative design to obtain and analyze the data. Observation and interview were used to collect the data. Non participant interview was chosen to get the data of teacher’s talk and the element of teacher’s talk used by the lecturer. Besides, the structured interview was used to gain the information of the teacher’s reason of using the most dominant element of teacher’s talk.